UWSNs: A Round-Based Clustering Scheme for Data Redundancy Resolve. (1st April 2014) - Tran, Khoa Thi-Minh; Oh, Seung-Hyun
Abstract : The underwater wireless sensor network (UWSN) is a state-of-the-art approach to exploring potential information and resources in the aquatic environment. However, underwater communication has unique features, such as long propagation delay, low bandwidth capacity, high bit error rates, and mobility, memory, and battery limitations. In this paper, we propose a round-based clustering scheme that can overcome the UWSN's confines mainly by resolving the transmission of redundant data in the network—one of the significant factors that reduces network lifetime. Our proposed scheme works in rounds, with each round consisting of four main phases: initialization, cluster-head selection, clustering, and data aggregation. Suitable mechanisms are chosen to apply in each round. By dealing with most of the redundant data, our proposed clustering scheme better reduces network consumption, thus increasing network throughput. Moreover, the minimum percentage of received data at the sink/base station is guaranteed.